Creating Markets in Morocco : A Second Generation of Reforms - Boosting Private Sector Growth, Job Creation and Skills Upgrading - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Morocco has steered significant resources towards large investments in economic sectors identified as strategic to growth, and for increased productivity and value addition. Despite Morocco’s strikingly high investment rate, one of the highest in the world at an average of thirty-four percent of gross domestic product (GDP) annually since the mid-2000s, the returns in economic growth, job creation and productivity, have been disappointing. The Moroccan economy has performed particularly poorly in terms of job creation. A more vibrant private sector is needed to create more jobs. This CPSD identifies policy recommendations and investment opportunities that would foster job creation by the formal private sector and improve labor supply in skills that would anchor Morocco as an emerging economy, to continue its path of growth, and to move into higher value-added and innovative sectors.